Ethnographic decision tree for male decision criteria related to online games. (1st October 2013) - Chuang, Tung-Lin; Su, Chung-Ho
Online games have emerged as an important and interesting research area in a variety of academic and official settings. This study adopts ethnographic decision tree modelling (EDTM) which here integrates qualitative and quantitative paradigms to model the decision-making process of whether or not to play online games by male undergraduate students. The model is built based on qualitative data gathered through in-depth interviews of 29 respondents, where 18 criteria for playing online games are elicited. The model is tested using qualitative and quantitative data from interviews, and a structured questionnaire involving 241 respondents. The predictability of the model is 90.04%. Armed with the results, this study provides online game industries an understanding of the decision-making process of male undergraduate players in Taiwan, and reveals methodology and theory standpoints for the researchers with similar interests.